# A.10.2 Section 10.2 Answers

$$\newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} }$$ $$\newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}}$$$$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\kernel}{\mathrm{null}\,}$$ $$\newcommand{\range}{\mathrm{range}\,}$$ $$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$ $$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}[1]{\| #1 \|}$$ $$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\kernel}{\mathrm{null}\,}$$ $$\newcommand{\range}{\mathrm{range}\,}$$ $$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$ $$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}[1]{\| #1 \|}$$ $$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$ $$\newcommand{\Span}{\mathrm{span}}$$$$\newcommand{\AA}{\unicode[.8,0]{x212B}}$$

1.

1. $$\bf{y'}=\left[\begin{array}{cc}{2}&{4}\\{4}&{2}\end{array}\right]{\bf y}$$
2. $$\bf{y'}=\left[\begin{array}{cc}{-2}&{-2}\\{-5}&{1}\end{array}\right]{\bf y}$$
3. $$\bf{y'}=\left[\begin{array}{cc}{-4}&{-10}\\{3}&{7}\end{array}\right]{\bf y}$$
4. $$\bf{y'}=\left[\begin{array}{cc}{2}&{1}\\{1}&{2}\end{array}\right]{\bf y}$$

2.

1. $$\bf{y'}=\left[\begin{array}{ccc}{-1}&{2}&{3}\\{0}&{1}&{6}\\{0}&{0}&{-2}\end{array}\right]{\bf y}$$
2. $$\bf{y'}=\left[\begin{array}{ccc}{0}&{2}&{2}\\{2}&{0}&{2}\\{2}&{2}&{0}\end{array}\right]{\bf y}$$
3. $$\bf{y'}=\left[\begin{array}{ccc}{-1}&{2}&{2}\\{2}&{-1}&{2}\\{2}&{2}&{-1}\end{array}\right]{\bf y}$$
4. $$\bf{y'}=\left[\begin{array}{ccc}{3}&{-1}&{-1}\\{-2}&{3}&{2}\\{4}&{-1}&{-2}\end{array}\right]{\bf y}$$

3.

1. $$\bf{y'}=\left[\begin{array}{cc}{1}&{1}\\{-2}&{4}\end{array}\right]{\bf y},\quad {\bf y}(0)=\left[\begin{array}{c}{1}\\{0}\end{array}\right]$$
2. $$\bf{y'}=\left[\begin{array}{cc}{5}&{3}\\{-1}&{1}\end{array}\right]{\bf y},\quad {\bf y}(0)=\left[\begin{array}{c}{9}\\{-5}\end{array}\right]$$

4.

1. $$\bf{y'}=\left[\begin{array}{ccc}{6}&{4}&{4}\\{-7}&{-2}&{-1}\\{7}&{4}&{3}\end{array}\right]{\bf y},\quad {\bf y}(0)=\left[\begin{array}{c}{3}\\{-6}\\{4}\end{array}\right]$$
2. $$\bf{y'}=\left[\begin{array}{ccc}{8}&{7}&{7}\\{-5}&{-6}&{-9}\\{5}&{7}&{10}\end{array}\right]{\bf y},\quad {\bf y}(0)=\left[\begin{array}{c}{2}\\{-4}\\{3}\end{array}\right]$$

5.

1. $${\bf y'}=\left[\begin{array}{cc}{-3}&{2}\\{-5}&{3}\end{array}\right] {\bf y}+ \left[\begin{array}{c}{3-2t}\\{6-3t}\end{array}\right]$$
2. $${\bf y'}=\left[\begin{array}{cc}{3}&{1}\\{-1}&{1}\end{array}\right]{\bf y} + \left[\begin{array}{c}{-5e^{t}}\\{e^{t}}\end{array}\right]$$

10.

1. $$\frac{d}{dt}Y^{2}=Y'Y+YY'$$
2. $$\frac{d}{dt}Y^{n}=Y'Y^{n-1}+YY'Y^{n-2}+Y^{2}Y'Y^{n-3}+\ldots + Y^{n-1}Y'=\sum_{r=0}^{n-1}Y^{r}Y'Y^{n-r-1}$$

13. $$B=(P'+PA)P^{-1}$$

This page titled A.10.2 Section 10.2 Answers is shared under a CC BY-NC-SA 3.0 license and was authored, remixed, and/or curated by William F. Trench.